2023
DOI: 10.18502/ijpa.v18i3.13755
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Associated Risk Factors of Parasites in Oral Cavity of Children with Malignancies in Western Iran

Fahimeh Kooshki,
Amal Khudair Khalaf,
Hossein Mahmoudvand
et al.

Abstract: Background: This survey was designed to study the molecular epidemiology and risk factors of Entamoeba gingivalis and Trichomonas tenax in children with underlying malignancies and those on chemotherapy in Lorestan province, West of Iran. Methods: The present cross-sectional descriptive study was performed on children who suffering from different types of malignancies or receiving treatment by chemotherapy referring to oncology section of hospitals of Lorestan Province, Iran during May 2021 to April 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the present study, although the prevalence of oral cavity parasites was higher in children less than 10 years old, this difference was not significant. Similarly, in the study conducted by Kooshki et al. (2023) showed that there was no considerable correlation between the gender and the prevalence of E. gingivalis and T. tenax parasites in children with cancer from Lorestan, Iran ( Kooshki et al., 2023 ).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In the present study, although the prevalence of oral cavity parasites was higher in children less than 10 years old, this difference was not significant. Similarly, in the study conducted by Kooshki et al. (2023) showed that there was no considerable correlation between the gender and the prevalence of E. gingivalis and T. tenax parasites in children with cancer from Lorestan, Iran ( Kooshki et al., 2023 ).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in the study conducted by Kooshki et al. (2023) showed that there was no considerable correlation between the gender and the prevalence of E. gingivalis and T. tenax parasites in children with cancer from Lorestan, Iran ( Kooshki et al., 2023 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations